Pelatihan Peningkatan Kapasitas Pemerintah Desa Melalui Pelatihan Website, Menuju Desa Digital Desa Air Dingin - Handayani, Sri; Hanila, Siti; Prawitasari, Andriyani; Fitriano, Yun; Wulandari, Weni (Universitas Dehasen Bengkulu, 2022)
Digital village is a program concept that implements a system of government services, community services, and community empowerment based on the use of information technology. This program aims to develop village potential, marketing and accelerate access and public services. The development of information and communication technology (ICT) has given rise to website media to inform everything via the internet. Utilization of Website information system media to inform village profiles and potential is also in line with Law no. 6 of 2014 concerning villages, where villages are entitled to greater access to obtain and disseminate development information. Based on this Law, Regional Governments are required to develop Village information systems and the development of Rural Areas independently or in collaboration with related institutions. As an effort to develop the Village Website application, this service proposes training activities for creating a village website to inform village profiles and potential in Air Cold Village, Sindang Kelingi District, Rejang Lebong Regency. Implementation of Community Service Activities (PKM) will be held on December 10, 2021 - January 10, 2022 at Air Cold Village, Bengkulu Province. All of these community service activities ran smoothly and were successful. The method used was lectures accompanied by direct practice for participants to be able to document information in the village into digital information and disseminated through the village website media. The results of this community service activity,Keywords: Village government, wabesite, Digita Village